Design of graphical user interface for multiuser SAC-OCDMA performance analysis - H Abdlkarem, Najla. (2015)
The transmission of data by multiple users simultaneously using various multiple access techniques over fibre optic communication has been studied in several literatures. It provides high data rates and leads to high total throughputs while taking advantage of high speed in optic fibre. In multiuser transmission using OCDMA, many codewords are sent simultaneously over the channel as a result of many active users and this can cause multi-user access interference between users. Spectral-amplitude-coding (SAC) OCDMA is used to cancel the effect of multiuser access interference using code sequence with in-phase cross correlation. Several OCDMA based on SAC OCDMA codes such as. Quadratic Congruence (QC), Extended Quadratic Congruence (EQC) and Modified Quadratic Congruence (MQC) proportion were investigated further and implemented. Furthermore, in the SAC-OCDMA, appropriate detection technique is required to reduce the multi-user access interference between users and extraction of user data. Three detection technique were considered AND, modified-AND and single photodiode detection (SPD) technique. In this project, the graphical user interface (GUI) was developed for multi-user OCDMA performance analysis using the matlab platform. This allowed for comparison in terms of length of code, data rate for multiple users.In addition , the performance of the decoder which is implemented using fiber Bragg gratings (FBGs) for the three detection techniques using numerical analysis have been developed for the GUI. The numerical analysis is based on the SNR and BER for the system in the presence of thermal noise, shot noise and phase induced intensity noise. Finally, The developed is GUI used to compare the performance of the QC, EQC and MQC codes, AND, modified-AND and SPD detection techniques. Result shows that MQC outperforms EQ and EQC codes when many active users transmitting. The SPD detection technique when modified double weight (MDW) code was used. has a better BER and SNR compared to the modified-AND and AND detection technique.